2002
DOI: 10.1021/cr010423z
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multifunctional Polymers from Aromatic Diamines by Oxidative Polymerizations

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
507
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 654 publications
(524 citation statements)
references
References 415 publications
(1,722 reference statements)
16
507
0
1
Order By: Relevance
“…The chemical and electrochemical oxidation of phenylenediamines has been extensively researched [35]. Chemical oxidation of p-phenylenediamines (p-PD) and N-substituted derivatives has been extensively explored due to its application in hair coloring and color photography [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The chemical and electrochemical oxidation of phenylenediamines has been extensively researched [35]. Chemical oxidation of p-phenylenediamines (p-PD) and N-substituted derivatives has been extensively explored due to its application in hair coloring and color photography [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical oxidation of p-PD in aqueous acidic medium produces p-benzoquinone as final product [38,40]. However, it has been reported that p-PD produces a polymeric powder by chemical oxidative polimerization [35,41]. The electro-oxidation of both m-phenylenediamine (m-PD) and o-phenylenediamine (o-PD) produces polymeric films [35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The peak at 1359 cm -1 and 1286 cm -1 are associated with C-N-C stretching in the benzenoid and quinoid rings 22 . Furthermore, the bands at 718 cm -1 and 609 cm -1 are the characteristic of C-H out-of-plane bending vibrations of benzene nuclei in the phenazine skeleton 23 . However with addition of SiO 2 nanoparticles, the characteristic peaks are slightly shifted to the lower wave numbers with slight increase in their intensities.…”
Section: Results and Discussion:-mentioning
confidence: 99%